Watkins Family 1926 Model T Ford - Watkins, Howard::::::::: (1988)
Back seat: Francis Kamp, Juanita Smith, and Marketa Smith; Front seat: Howard Watkins and Robin Watkins Parked in front of Watkins home at 3506 E. Balch Avenue